Estrategia de intervención psicopedagógica para atender la timidez en adolescentes - Barrionuevo Alvarado , Karem Kadecsi (2025)
The present research aims to design a psycho-pedagogical intervention strategy to promote social participation and overcoming shyness in the school environment, in adolescents of the ninth year of General Basic Education of the Educational Unit “Quevedo” during the period 2024-2025 , with the purpose of improving social interaction, self-esteem and confidence of adolescents , likewise, it aims to identify the factors that influence the development of learning and daily difficulties associated with shyness. To address this problem, a study was conducted with a qualitative approach using different techniques such as interview, survey and observation techniques, in a sample of 20 students, between 13 and 14 years old. The results obtained indicate that shyness is perceived as a problem both in the personal and social sphere, generating difficulties in the relationship between teachers and classmates. Most of the respondents consider that this is an issue that affects the personal and social environment, and therefore prefer that this issue be addressed in the educational units by specialists in the area who, through appropriate strategies, could reduce this behavior and improve the socioemotional, psychological and pedagogical development of adolescents. . In conclusion, it is evident that a well-structured psycho-pedagogical intervention adapted to the needs of adolescents can generate the greatest interaction during the teaching-learning process, improving the educational and social quality of life of adolescents.